ANALISIS KELAYAKAN USAHA PEMBENIHAN IKAN KOI (CYPRINUS CARPIO) DI BALAI BENIH IKAN (BBI) BATU KUMBUNG, KECAMATAN LINGSAR - Sahrul Alim; Nuri Muahiddah (Jurnal Media Akuakultur Indonesia, 2023)
Koi fish (Cyprinus carpio) is one of the potential freshwater ornamental fish commodities that can be cultivated. This freshwater ornamental fish has several advantages, including easy maintenance, ability to survive in low oxygen water, and ability to produce high-quality eggs. The purpose of this research is to assess the feasibility of the breeding activities conducted at BBI Batu Kumbung through economic analysis. The research method used in this study is "Descriptive Comparative Method". Based on the research findings the economic analysis conducted includes assumptions, Total Costs Rp. 39.304.000, Sales Revenue Per Cycle Rp. 64.200.000, Income Per Cycle Rp. 24.896.000, R/C Ratio 1.63, Break-Even Point Price Rp. 1.224 per fish, Break-Even Point Production 19.652 and Payback Period 6.3 months. Based on the business analysis, the production of koi fish seeds at BBI Batu Kumbung can be considered feasible and has the potential for development, as it can provide good profits with a good Return on Investment (ROI).